Coherent phonon scattering in ZnO and ZnS at sulfite and oxygen impurities. Issue 1 (20th September 2012) - Bachmann, M.; Czerner, M.; Heiliger, C.
Abstract We employ an atomistic Green's function (AGF) method which is based on ab initio interatomic force constants (IFCs) to calculate coherent phonon scattering in ZnO at sulfur impurities and ZnS at oxygen impurities. For our calculations we consider different geometries and different transport directions. In particular, we investigate the impact of the change in the mass of the impurities on the transmission function and also the change in the IFCs due to the impurities. We show that if we only consider a change in the mass the transmission function for the high energy phonons is strongly reduced. If we further take into account the change in the IFCs also the low energy phonons are affected. From these results we conclude that incorporation of sulfur in ZnO and incorporation of oxygen in ZnS can reduce the thermal lattice conductivity and therefore increase the figure of merit substantially. In addition, our results demonstrate that for a realistic description just the change of the mass is not enough but the IFCs of the impurities have to be calculated.